Antemortem Injuries or Postmortem Mutilation?- A Case Report - Hinnawi S, Al; SR, Kolle; RB, Sukhdeve; SS, Sonawane; C , Wood (Journal of Indian Academy of Forensic Medicine, 2024)
Only a few cases of homicidal decapitation have been sporadically reported in Forensic literature. Sometimes, the autopsy surgeon may  encounter cases in which the distinction between a vital or post-mortem phenomenon is arduous. Suicides by self-decapitation have been  reported in India, for instance, individuals deliberately place their necks onto the railway track while a train is approaching. Also,  unintentional decapitations are possible in cases of suicide as in hangings. Accidental decapitation may also occur, for example, in train  fatalities, industrial accidents and injuries during road and motor vehicular accidents. The most exceptional cases are homicidal  decapitation. It has been used as a manner of death to carry out executions for centuries and is still used in some countries today.  Dismemberment or post-mortem mutilation of a corpse has always been viewed as more appalling than the homicide itself. It usually  occurs when the killing takes place without any prior planning. In this report, an 80-year-old female was decapitated and found in a  mutilated state. It was determined that the victim was decapitated and dismembered by her 25-year-old grandnephew, who was receiving  treatment for psychiatric illness on and off for the past 10 years and had just been discharged from the inpatient mental health facility only  the previous day. Decapitation along with other post-mortem mutilations were present on the body. The motives for dismemberment and  decapitation are considered to be aggressive, defensive, and offensive. The combination of history, crime scene findings, and autopsy  findings will help to distinguish the mode as well as the nature of the injury whether antemortem or post-mortem. Moreover, we also wish  to highlight the role of psychiatric illness and especially the importance of swift intervention and treatment.
Keywords: Decapitation; Mutilation; Dismemberment; Homicide; Parricide; Mental illness